2022
DOI: 10.1039/d2sc03998b
|View full text |Cite
|
Sign up to set email alerts
|

High spin Fe3+-related bonding strength and electron transfer for sensitive and stable SERS detection

Abstract: The intrinsic electronic states of transition metal-containing SERS substrates, especially the effect of spin state on the detection sensitivity still remains unknown. Herein, we propose a simple co-precipitation approach to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…[53][54][55]69 In addition to semiconductors, other materials with highly tunable structural properties, such as MOFs and carbonaceous nanomaterials, have also been employed as SERS substrates. [56][57][58][59][60] For example, we extended the concept of enhanced light-matter interaction to enhance SERS sensitivity in chiral carbonaceous nanotubes by leveraging birefringence induced by the helical structure. 59 Furthermore, we demonstrated that FeNiTi-MIL-101, with an increased amount of high-spin Fe 3+ , exhibited higher SERS sensitivity compared to Fe-MIL-101, owing to the enhanced charge transfer efficiency.…”
Section: Development Of Versatile Sers Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…[53][54][55]69 In addition to semiconductors, other materials with highly tunable structural properties, such as MOFs and carbonaceous nanomaterials, have also been employed as SERS substrates. [56][57][58][59][60] For example, we extended the concept of enhanced light-matter interaction to enhance SERS sensitivity in chiral carbonaceous nanotubes by leveraging birefringence induced by the helical structure. 59 Furthermore, we demonstrated that FeNiTi-MIL-101, with an increased amount of high-spin Fe 3+ , exhibited higher SERS sensitivity compared to Fe-MIL-101, owing to the enhanced charge transfer efficiency.…”
Section: Development Of Versatile Sers Substratesmentioning
confidence: 99%
“…59 Furthermore, we demonstrated that FeNiTi-MIL-101, with an increased amount of high-spin Fe 3+ , exhibited higher SERS sensitivity compared to Fe-MIL-101, owing to the enhanced charge transfer efficiency. 60 In addition to single component materials, various multicomponent materials, including SnO 2 -NiO x /Cu, Mo-doped Ta 2 O 5 , metal@MOF and metal/graphene, have been developed as SERS substrates. [61][62][63][64][65] We made a breakthrough for the detection of nonchemisorbing volatile organic compounds (VOC) such as toluene through constructing a core-shell structured ZnO@ZIF-8.…”
Section: Development Of Versatile Sers Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, MIL-101(Fe) is more likely to accept electrons under pressure, while MIL-101(Cr) is more likely to donate electrons for H 2 O 2 synthesis. 21,22…”
mentioning
confidence: 99%
“…Consequently, MIL-101(Fe) is more likely to accept electrons under pressure, while MIL-101(Cr) is more likely to donate electrons for H 2 O 2 synthesis. 21,22 MIL-101(Cr) exhibits a phase-voltage hysteresis loop with a 1801 change under a 5 V direct current bias field (blue line in Fig. 2d), displaying a distinct hysteresis with local polarization switching behavior.…”
mentioning
confidence: 99%